Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1017/s1041610208008387
|View full text |Cite
|
Sign up to set email alerts
|

Training in dementia care: a cluster-randomized controlled trial of a training program for nursing home staff in Germany

Abstract: Results of the study indicate both the effectiveness and the limitations of a general training program in dementia care. The complexity of the nursing home setting potentially needs more complex interventions. Ongoing and continued support of the caregivers, as well as changes in organization and environment, are more likely to be helpful in the long-term improvement in the quality of care. Future research should focus on studies of specific interventions, such as the interesting effects of relaxation training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(147 citation statements)
references
References 38 publications
(44 reference statements)
5
136
1
4
Order By: Relevance
“…Eight studies were carried out in the USA, three in Germany (Haberstroh et al, 2006;Kuske et al, 2009), and one in the UK (Done and Thomas, 2001). Six studies (McCallion et al, 1999;Burgio et al, 2001;Teri et al, 2005;Haberstroh et al, 2006; compared the communication skills intervention to routine care or no intervention and three studies used a placebo control group setting (Done and Thomas, 2001;Magai et al, 2002;Kuske et al, 2009).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were carried out in the USA, three in Germany (Haberstroh et al, 2006;Kuske et al, 2009), and one in the UK (Done and Thomas, 2001). Six studies (McCallion et al, 1999;Burgio et al, 2001;Teri et al, 2005;Haberstroh et al, 2006; compared the communication skills intervention to routine care or no intervention and three studies used a placebo control group setting (Done and Thomas, 2001;Magai et al, 2002;Kuske et al, 2009).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Overall sample size varied from six (Teri et al, 2005) to 96 professional caregivers (Kuske et al, 2009). Most interventions included clinical nursing assistants (CNAs) and licensed practical nurses (LPNs).…”
Section: Study Participantsmentioning
confidence: 99%
“…The measurement of distal outcomes of health-care training is challenging. In the Older People's Services and Workforce Interventions: a Synthesis of Evidence (OPSWISE) study for clinical support workforce developments, 51 of the 76 papers identified, only two were reports of randomised controlled trials (Kuske et al 52 and Clare et al 53 ) and only one observed level 4 (care home resident) outcomes. 53 The Kirkpatrick training evaluation model has been criticised for a lack of attention to the environment in which trainee skills are practised.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…As pessoas idosas com PNC perdem progressivamente as suas capacidades cognitivas e motoras, originando, em estados mais avançados da doença, um elevado sentimento de sobrecarga na família, que culmina frequentemente com a sua institucionalização. De acordo com Kuske et al (2009), cerca de 60% das pessoas institucionalizadas em países industrializados apresenta um quadro demencial, o que acarreta novos desafios para estas instituições e para os seus profissionais. Assim, perante as alterações demográficas que estão a ocorrer e os aspetos da vulnerabilidade associados ao envelhecimento, torna-se, sem dúvida, cada vez mais importante equacionar os cenários que podem influenciar positivamente a qualidade de vida na velhice e que partem da adoção de princípios de cuidados centrados na pessoa e destinados à promoção da dignidade humana.…”
Section: Introductionunclassified